The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1111/j.1365-2621.2001.tb04620.x
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulating Properties of Whey Protein Concentrate 75

Abstract: Emulsions containing various levels of soya oil dispersed in solutions of whey protein concentrate (WPC) 75 (5% w/v) were spray-dried to yield powders with oil contents ranging from 20% to 75% (w/w). The effect of homogenizing pressure and oil/protein ratio on oil globule size distributions and protein load of the emulsions and the microencapsulation efficiency (ME) and redispersion behavior of the powders were examined. Emulsion oil droplet size decreased with increasing homogenization pressure but was not af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
46
2
8

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 25 publications
(17 reference statements)
11
46
2
8
Order By: Relevance
“…[25,26] suszyli rozpyłowo emulsje, w których fazę zdyspergowaną stanowił olej sojowy w proporcji do składnika białkowego od 0,25 do 3,0. Średnia średnica objętościowa kuleczek olejowych w emulsji przed suszeniem zmniejszała się wraz ze zwiększającym się od 10 do 50 MPa ciśnieniem homogenizacji (przy czym w mniejszym stopniu przy ciśnieniu >30 MPa) i była niezależna od stosunku olej : białko.…”
Section: Homogenizacja Emulsjiunclassified
See 2 more Smart Citations
“…[25,26] suszyli rozpyłowo emulsje, w których fazę zdyspergowaną stanowił olej sojowy w proporcji do składnika białkowego od 0,25 do 3,0. Średnia średnica objętościowa kuleczek olejowych w emulsji przed suszeniem zmniejszała się wraz ze zwiększającym się od 10 do 50 MPa ciśnieniem homogenizacji (przy czym w mniejszym stopniu przy ciśnieniu >30 MPa) i była niezależna od stosunku olej : białko.…”
Section: Homogenizacja Emulsjiunclassified
“…[25] studiowali właściwości kapsułkujące koncentratu białek serwatkowych WPC75 w układach, w których fazę zdyspergowaną stanowił olej sojowy i stosunek zawartości oleju do białka zmieniał się w szerokim zakresie od 0,25 do 3,0, co odpowiadało zawartości oleju w proszku od 20 do 75 %. Zadowalającą efektywność uzyskiwano przy stosunku olej : koncentrat białek <0,75.…”
Section: Rola Składników Emulsji W Mikrokapsułkowaniu Tłuszczuunclassified
See 1 more Smart Citation
“…Sample EPO-4 was also homogenized before freeze-drying, but in this case, the difference in data between the samples results rather from process parameters of drying. Hogan et al (2001) found that moisture contents of spray-dried soya oil emulsions encapsulated with whey protein concentrate (WPC) were not affected by homogenization pressure or oil/protein ratio. These authors reported also that homogenization pressure higher than 100 bar had no effect on encapsulation efficiency of soybean oil with sodium caseinate.…”
Section: Impact Of Emulsion Treatment Before Dryingmentioning
confidence: 99%
“…Increasing the hydrophobic/aqueous phase ratio did not significantly affect the fat globule size, even at high internal mixing speeds. Hogan et al [14] recently reported that particle size of soya oil/whey protein emulsions decreased with increasing homogenization pressure but was not affected by oil/protein ratios ranging from 0.25 to 3.0. The highest oil/protein ratio (w/w) tested in our study was 1.11, which was much less than the values normally used (up to 12.5) to examine emulsifying properties of whey proteins [6,9,10].…”
Section: Effects Of Emulsification Conditions On Fat Globule Size Dismentioning
confidence: 99%